Konsep Poligami Dalam Perspektif Hukum Islam dan UU No. 1 Tahun 1974 dan Penerapannya di Kota Bogor - Al Farisi, Salman; Gustiawati, Syarifah; Kosim, AhmadÂ Mulyadi (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2022)
The study examined "the concept of polygamy in the perspective of islamic law and law no. One year of 1974 and application to bogor city." More detailed deals with the application of polygamy in bogor city both in concepts and practices in the field. Islam strictly stresses that when it comes to polygamy and is concerned that it cannot be fair it is enough with one wife. These studies are being reviewed using qualitative research methods. The kind of approach the author USES is yuridis and normatif islamic law, an approach that reviews and analyzes the problem using principles and based on data of literature through library research. This study emphasizes aspects of juridical Islam and law, by looking at its regulatory regulations and their feeding, and by the islamic law that make its values an object of research. The concept of polygamy according to islamic law is explained in god's word letter a-nisa verse 3 and according to statute no. 1 of 1974 is explained in chapter 3 verse 2 of 1974's no. 1 law on marriage, that is, courts can permit a husband to have more than one wife if desired by those involved. The practice of polygamy in the city of bogor was prescribed that a husband who was to be married to more than one should get permission from a religious court. Keyword: Polygamy, Law No. 1 Year 1974, Islamic Law